2016
DOI: 10.1155/2016/6954758
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Morbidity in Solid Organ Injuries

Abstract: Background and Aim. The aim of this study was to investigate the effects of demographic characteristics, biochemical parameters, amount of blood transfusion, and trauma scores on morbidity in patients with solid organ injury following trauma. Material and Method. One hundred nine patients with solid organ injury due to abdominal trauma during January 2005 and October 2015 were examined retrospectively in the General Surgery Department of Dicle University Medical Faculty. Patients' age, gender, trauma interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…Mysore et al have reported that patients with the highest expression of PD-1 + Tim-3 + T cells in the memory compartment before LTx had increased incidence of infections after LTx, especially within the first 90 days [ 13 ]. The evaluation of T cell subsets has played an important role in predicting post-transplant infections and allograft rejections in transplant recipients [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mysore et al have reported that patients with the highest expression of PD-1 + Tim-3 + T cells in the memory compartment before LTx had increased incidence of infections after LTx, especially within the first 90 days [ 13 ]. The evaluation of T cell subsets has played an important role in predicting post-transplant infections and allograft rejections in transplant recipients [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although we did not find a significant difference in the hemoglobin levels between the patients with and without mortality, we found higher transfusion rates in patients with mortality mean 8.8 units of ES versus 3.3 units of ES). Similarly, Baygeldi et al [19] have found four times more erythrocyte transfusion in patents with morbidity following management of solid organ injuries following blunt and penetrating abdominal trauma.…”
Section: Discussionmentioning
confidence: 85%
“…Hemodynamic parameters of the patients have been shown to increase the mortality risk of the patients. [2,3,19] Systolic blood pressure has been frequently reported parameter, and blood pressures below 60-90 mmHg have been shown to increase mortality nearly four times, [2,3] We evaluated the differences in mean arterial pressures between patients with and without mortality. We found that patients with mortality had significantly lower mean arterial pressure when compared to patients without mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of early diagnosis using angiography is shown in studies where extravasation at the time of admission was found to be highly associated with the possibility of treatment, such as delayed splenectomy. [ 15 , 16 ]…”
Section: Discussionmentioning
confidence: 99%